Monologue of Discernment About Dark Matter (Global Journal of Science Frontier Research, 2025)
The aim of this work on DM is to confine it whether it belongs to the dark periodic table or is part of a single very small dark element as mentioned in [10] making it possible to improve the works presented by the undersigned in the bibliography for example teleportation [7] could be improved with elements inserted in a certain way from the dark periodic table: in the W spiral of the classical periodic table, or in the antigravity ' Poynting vector' in fig. 3 [5].
Keywords: artificial intelligence vs multiple sclerosis